Differential regulation of lymphatic junctional morphology and the potential effects on cardiovascular diseases - Peluzzo, Amanda M.; Bkhache, Meriem; Do, Long Nguyen Hoang; Autieri, Michael V.; Liu, Xiaolei (Frontiers in Physiology, 2023)
The lymphatic vasculature provides an essential route to drain fluid, macromolecules, and immune cells from the interstitium as lymph, returning it to the bloodstream where the thoracic duct meets the subclavian vein. To ensure functional lymphatic drainage, the lymphatic system contains a complex network of vessels which has differential regulation of unique cell-cell junctions. The lymphatic endothelial cells lining initial lymphatic vessels form permeable “button-like” junctions which allow substances to enter the vessel. Collecting lymphatic vessels form less permeable “zipper-like” junctions which retain lymph within the vessel and prevent leakage. Therefore, sections of the lymphatic bed are differentially permeable, regulated in part by its junctional morphology. In this review, we will discuss our current understanding of regulating lymphatic junctional morphology, highlighting how it relates to lymphatic permeability during development and disease. We will also discuss the effect of alterations in lymphatic permeability on efficient lymphatic flux in health and how it may affect cardiovascular diseases, with a focus on atherosclerosis.